Multifunctional luminescent molecules of o-carborane-pyrene dyad/triad: flexible synthesis and study of the photophysical properties. (July 2018) - Wu, Xueyan; Guo, Jixi; Zhao, Jianzhang; Che, Yuanyuan; Jia, Dianzeng; Chen, Yi
Abstract: The development of organic single-molecule multiple photoluminescence compounds hold a great promise for advanced opt-electronic devices, optical probes and temperature sensors. The pyrenyl-substituted o -carborane, CSP andCDP, were obtained via a modified nickel-catalyzed cross-coupling reaction in satisfactory yields. Based on variety of spectroscopic measurements, it was found that theCSP andCDP exhibit multifunctional luminescent properties, such as dual emissions as well as thermochromic luminescence between orange and blue forCSP, ternary species emissions forCDP, and aggregation induced emission (AIE) and AIE enhancements (AIEE) properties for both. The origination of the multiple photoluminescence attributes was investigated deeply. We demonstrated that the multiple photoluminescence in the pyrenyl-substituted o -carborane rose from the electronic interaction between pyrenyl and o -carboranyl leading to the formation of ICT state, and the mono-molecular excimer emission attributed to the interaction between the conformational of two "face−to−face" pyrene chromophores. In addition, clear thermochromic luminescence properties were caused by ICT at room temperature and excimer formation at 77 K in the solid state. The results are useful as a guideline for designing luminescent solid materials with multiple photoluminescence and thermochromic luminescence properties. Graphical abstract: Highlights: Pyrenyl-substituted- ortho -carboranes, which were synthesized by a modified nickel-catalyzed cross-coupling reaction between pyrene and o -carborane, showed unique multifunctional photoluminescence behaviors. It is the first time that achieving the multiple emissive species of pyrene fluorophores using o-carborane and the multiple photoluminescence properties were studied by variety of spectroscopic measurements and theoretical calculations. The thermochromic luminescence properties were caused by intramolecular charge transfer (ICT) at room temperature and excimer formation at 77 K in the solid state.